2003
DOI: 10.5551/jat.10.117
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Rho A and Rho Kinase to Platelet-Derived Growth Factor-BB-Induced Proliferation of Vascular Smooth Muscle Cells.

Abstract: In order to identify small G protein (s) which contributes to the proliferation of vascular smooth muscle cells (VSMCs), we examined the effect of an HMG-CoA reductase inhibitor (cerivastatin), a farnesyltransferase inhibitor (FTI-277), a geranyl geranyl transferase inhibitor (GGTI-286) and a Rho kinase inhibitor (Y-27632) on the proliferation of cultured rat VSMCs stimulated with 20ng/ml platelet-derived growth factor (PDGF)-BB. Cerivastatin and GGTI-286, but not FTI-277, suppressed the PDGF-BB-induced activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 31 publications
1
33
1
Order By: Relevance
“…Furthermore, similar results were obtained for ERK activity that is known to be important for VSMC migration and proliferation. [33][34][35] However, we observed less dramatic changes in ROCK and ERK activities compared with those in the degree of PH, which could be explained by the fact that we used whole mouse lung tissue for Western blot that contains not only VSMC but also many other types of cells. In addition, we confirmed that pulmonary arteries from patients with IPAH revealed enhanced ERK activity.…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, similar results were obtained for ERK activity that is known to be important for VSMC migration and proliferation. [33][34][35] However, we observed less dramatic changes in ROCK and ERK activities compared with those in the degree of PH, which could be explained by the fact that we used whole mouse lung tissue for Western blot that contains not only VSMC but also many other types of cells. In addition, we confirmed that pulmonary arteries from patients with IPAH revealed enhanced ERK activity.…”
Section: Discussionmentioning
confidence: 53%
“…4). Therefore, our result shows that the change of Rho-kinase activation does not appear in the early stages of atherosclerosis, although involvement of the kinase in the disease has been reported previously 20,[37][38][39][40] ; however, we are not able to reject the alterations of other contractionrelated signal pathways in the early stage of the syndrome. The decrease in PE-induced maximal contraction in apoE-KO mouse aorta suggests that the Rho/ Rho-kinase-independent signal pathway is impaired in the early stage of atherosclerosis.…”
Section: Discussioncontrasting
confidence: 36%
“…p38 MAPK is also reportedly involved in Rho-kinase-mediated epithelial-mesenchymal transition (35), production of profibrotic mediators (41), and neuronal degeneration (49). Moreover, ERK, another member of the MAPK family, has been implicated in Rho/Rho-kinase-induced proliferation of vascular smooth muscle cells (16). These findings indicate that MAPKs are important mediators of the Rho/Rhokinase pathway and that individual MAPKs make distinct contributions to Rho/Rho-kinase signaling in a variety of contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the Rho/Rho-kinase pathway leads to the phosphorylation of downstream substrates, including myosin phosphatase target subunit (19), which has been postulated to control a variety of cellular functions such as cell proliferation, contraction, migration, and transcriptional regulation (8). A series of recent animal model studies have implicated Rho/Rho-kinase signaling in cardiovascular (16,44) and renal (34,36) disease. Furthermore, studies from our own laboratory and others have shown that pharmacological inhibition of Rho-kinase in experimental models of diabetes results in a significant reduction in albuminuria, accumulation of glomerular matrix (29), and infiltration of macrophages (18).…”
mentioning
confidence: 99%